„Lex Clodia de Cypro et exsulibus Byzantinis” — rzymski imperializm na styku prawa i polityki - Dominik Pieniądz (Prawo)
The article discusses the circumstances of the introduction of Clodian law on the annexation of Cyprus and the restoration of exiles from Byzantium, its provisions, and its significance in the context of Roman internal and foreign policy. The analysis also focuses on the motives behind passing the law, its legal form and the legal basis for the Roman annexation of Cyprus. Lex Clodia de Cypro et exsulibus Byzantinis is analysed as a case study of late Republican imperialism, primarily in terms of political and constitutional disputes over the decisive voice in foreign policy and organizational form of the Imperium Populi Romani.